PENANAMAN SIKAP PRO-LINGKUNGAN MELALUI PENGEMBANGAN DESA WISATA “KAMPOENG KALEN” DI DUSUN DANEN - Ayu Rahayu; eko yuliyanto (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2018)
Danen is located in Sumberadi village, Mlati sub-district, Sleman district, Daerah Istimewa Yogyakarta (DIY) Province. This hamlet has the potential of good natural resources and human resources especially active youth. However, this potential is not balanced with the attitude of people who are less concerned about the environment (pro-environment). The presence of littering and degradation of watersheds is a form of the necessity of planting a pro-environment attitude of the community. The development of tourist village "kampoeng kalen" is one of the right solutions in accordance with the potential owned by the hamlet. Through the development of tourist village "kampoeng kalen", youths move to be pro-environment agents for the whole village community in particular and the village in general. The method of implementation of this program is in the form of counseling, education, and continuous facilitation. The successful development of tourist village "kampoeng kalen" in instilling a pro-environment attitude is characterized by the state of the environment is more beautiful and community activities that pay more attention to aspects of concern for the environment.